1993
DOI: 10.1105/tpc.5.1.87
|View full text |Cite
|
Sign up to set email alerts
|

MsERK1: a mitogen-activated protein kinase from a flowering plant.

Abstract: The induction of proliferation and differentiation in cultured mammalian cells is mediated by a cascade of protein phosphorylations. A key enzyme in this signaling pathway is mitogen-activated protein (MAP) kinase (or ERK, extracellular signal-regulated kinase). We report the recovery of a full-length cDNA clone encoding a MAP kinase from alfalfa. We have named the 44-kD protein encoded by this clone MsERK1. Recombinant MsERKl (rMsERKl), when overexpressed in fscherichia coli, is recognized by antibodies raise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
78
0

Year Published

1993
1993
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(80 citation statements)
references
References 60 publications
2
78
0
Order By: Relevance
“…6C) (9,12,30). cDNAs that encode plant homologs of MAP kinase have recently been isolated from Medicago sativa (alfalfa) (7) and Arabidopsis thaliana (35), and protein kinase activity of the product from theArabidopsis cDNA was shown to be activated by animal MAPKK (35 …”
Section: Discussionmentioning
confidence: 99%
“…6C) (9,12,30). cDNAs that encode plant homologs of MAP kinase have recently been isolated from Medicago sativa (alfalfa) (7) and Arabidopsis thaliana (35), and protein kinase activity of the product from theArabidopsis cDNA was shown to be activated by animal MAPKK (35 …”
Section: Discussionmentioning
confidence: 99%
“…A unique characteristic of MAP kinases is reflected in the fact that their activities are regulated by the simultaneous phosphorylation of tyrosine and threonine residues by upstream protein kinases in a conserved sequence (Payne et al, 1991;Gartner et al, 1992;Posada and Cooper, 1992). This conserved sequence has been found in all of the amino acid sequences deduced from cDNA clones for MAP kinases of plants (Duerr et al, 1993;Jonak et al, 1993;Stafstrom et al, 1993;Wilson et al, 1993;Mizoguchi et al, 1994). Wilson et al (1993) reported that a homolog of the MAP kinase in tobacco is expressed in suspension-cultured tobacco cells.…”
Section: Discussionmentioning
confidence: 99%
“…Wilson et al (1993) reported that a homolog of the MAP kinase in tobacco is expressed in suspension-cultured tobacco cells. Duerr et al (1993) demonstrated that the tyrosine residue in the conserved sequence is crucial for the activity of a recombinant MAP kinase of alfalfa expressed in Escherichia coli, and the phosphorylated tyrosine residues in the protein are recognized by a phosphotyrosinespecific antibody. However, tyrosine phosphorylation of a regulatory protein in an extract of a higher plant has rarely been detected by immunoblotting with phosphotyrosine-specific antibodies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Self-incompability [3], initiation of mitosis [4,5], isoprenoid biosynthesis [6], cytoplasmic streaming [7,8], sucrose phosphate synthase activity [9], MSERK1 activity [5] and phosphoenolpyruvate carboxylase activity [10] are the examples of regulation of cellular responses that involved protein kinases. ZmPK1 kinase with the identical extracellular domain of Slocus glycoproteins [SLG] in Brassica species is involved in the selfincompability expression in pistils [11].…”
Section: Plant Protein Kinases In Various Signal Transduction Processesmentioning
confidence: 99%